Haemostatic disturbances in patients bitten by Russell's viper (Vipera russelli siamensis) in Burma. - Than-Than; Hutton, R; Myint-Lwin; Khin-Ei-Han; Soe-Soe; Tin-Nu-Swe; Phillips, R; Warrell, D (1988)
Patients who are severely envenomed by Russell's viper develop DIC which is frequently associated with spontaneous bleeding and incoagulable blood. These haemostatic disturbances may be responsible for death or organ/tissue damage both through haemorrhage and microvascular occlusion by fibrin thrombi. The most striking laboratory features of the coagulopathy developing after Russell's viper bite in the 42 patients studied were depletion of fibrinogen (mean 0.09 g/l, range 0-0.6), factor V (6.5 u/dl, range 0-17), factor X (35 u/dl, range 1-85), factor XIIIa (57 u/dl, range 15-82), plasminogen (61 u/dl, range 10-92), antiplasmin (36 u/dl, range 14-62). Protein C (49 u/dl, range 15-100) and platelets (104 x 10(9)/l, range 25-197). Intense fibrinolytic activity was detected in all cases with marked elevation of FDPs (1614 micrograms/ml, range 350-3000), a large proportion of which were cross-linked (1058 micrograms/ml, range 38-3000). The monospecific Burmese antivenom appeared to be very effective in neutralizing the venom procoagulants and in restoring blood coagulability. Moreover, the unexpectedly normal level of AT III provides a theoretical basis for the use of heparin to enhance the inactivation of those serine proteases present before antivenom administration.